2012
DOI: 10.1001/archinternmed.2011.1029
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Leg Cramps and Prescription Use That Precedes Them

Abstract: Cramp treatment was substantially more likely in the year following introduction of LABAs, potassium-sparing diuretics, or thiazidelike diuretics, and 60.3% of quinine users (individuals experiencing cramp) received at least 1 of these medications during a 13-year period. In contrast, statin and loop diuretic associations were small. Physicians should be mindful that the use of these medications may worsen symptoms in patients experiencing nocturnal leg cramps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 19 publications
2
59
0
4
Order By: Relevance
“…Other associations with NLC include female sex, leg claudication, electrolyte imbalance, pregnancy, peripheral neuropathy, peripheral vascular disease, angina, and arthritis[8]. Potential medication etiologies include inhaled long-acting beta-agonists, statins, and diuretics[9]. Existing prevalence data suggest that 37–50% of older adults have such leg cramps[4, 5, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Other associations with NLC include female sex, leg claudication, electrolyte imbalance, pregnancy, peripheral neuropathy, peripheral vascular disease, angina, and arthritis[8]. Potential medication etiologies include inhaled long-acting beta-agonists, statins, and diuretics[9]. Existing prevalence data suggest that 37–50% of older adults have such leg cramps[4, 5, 10].…”
Section: Introductionmentioning
confidence: 99%
“…6 Therefore, new quinine prescriptions are an excellent marker for new or escalating treatment of leg cramps, and we previously used these data to assess the potential cramp-promoting effects of commonly used medications. 7 We also looked for evidence of seasonality more generally (i.e., all Seasonal effects on the occurrence of nocturnal leg cramps: a prospective cohort study Background: It has been anecdotally reported that nocturnal leg cramps in pregnant women are worse in summer. We analyzed population-level data to determine whether the symptom burden of nocturnal leg cramps is seasonal in the general population.…”
Section: Data Sourcesmentioning
confidence: 99%
“…7 This is relevant because both of these drug classes can also be assumed to have some seasonality in their use. Specifically, use of β-agonists can be expected to increase in winter, when respiratory infections peak, and use of diuretics can be expected to peak in summer, when patients often mention ankle swelling (unpublished clinical observations).…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…All three classes of diuretics can cause muscle cramps, suggesting that reduced potassium and magnesium levels are not the sole cause [62,63]. Volume contraction might be a factor.…”
Section: Muscle Crampsmentioning
confidence: 99%